JURIDICAL REVIEW OF LEGAL PROTECTION OF HEALTH PERSONNEL ACCORDING TO INTERNATIONAL AND NATIONAL LAW - Ari Andayani; Agus Kurniawan (Transpublika Publisher, 2023)
Health represents a fundamental ideal of the Indonesian nation and serves as an embodiment of human rights. To ensure a high standard of health, the role of Health Workers is pivotal. However, several incidents have highlighted the prosecution or attacks on these workers during the provision of services, revealing a deficiency in both national and international legal protections. This research aims to analyze the legal protection arrangements for health workers in accordance with National and International Law, as well as identify the factors contributing to the non-compliance with legal protection regulations for health workers. The research is of a normative legal nature, employing a statutory and case-based approach. Data was collected through a comprehensive literature review using qualitative descriptive analysis. The findings of the study indicate that the legal protection for health workers has been outlined in National Law under Law no. 36 of 2014, while International Humanitarian Law serves as the framework for granting legal protection to Health Workers on an international scale. Factors contributing to the non-compliance with national legal protection regulations for Health Workers include Educational, Trust, and Environmental Factors. On the other hand, the non-compliance with legal protection regulations for Health Workers in the context of international law is primarily due to a lack of understanding and awareness of International Humanitarian Law, compounded by the challenges faced during times of conflict between nations.